The Relationship of Health Behavior with the Area of Sugar Content and Quality of Life of Diabetes Patients - Sasmiyanto Sasmiyanto (JURNAL KESEHATAN PRIMER, 2019)
Background: Having type 2 diabetes mellitus would be a pshycologically threat for diabetic patients. This study was conduct to investigate the correlation between health behavior towards blood glucose and quality of life of diabetic patients. Method: This study is correlational study conducted with cross sectional approach. It is involving 100 respondents of diabetic patient who involved in Prolanis Programme and was taken by purposive sampling. The data was taken by using questionnaires and gluco test and the analysed by using Spearman Correlation Test. Result: The results show p value of 0.000 and coefficient correlation of 0.724 for health behavior and blood glucose consentration. In the other hand the results show p value 0.000 and coefficient correlation of 0.892 for health behavior anf quality of life. It mean that there are significant and positively correlationship between health behavior towards blood glucose and quality of life of diabetic patients. Conclusion: The health care providers should pay attention to psychological aspect of diabetic clients since it proven to have contribution towards the controlling of blood glucose and their quality of life.